Teaching Languages for Specific and Academic Purposes in Higher Education - English, Deutsch, Italiano - Ballarin, Elena (Konferenzbeiträge / Atti / Proceedings, 2020)
The international symposium "Teaching Languages for Specific and Academic Purposes" aimed to bring together university instructors and researchers of LSP and LAP in order to share and explore approaches, methods, and practices which have emerged within diverse contexts. Topics include needs analyses, TBLT, curriculum development, collaborative reflective writing, correction codes, specific communication skills and competences, institutional challenges, technology and digital literacies, word lists, reading skills, textbooks, L1 transfer, academic writing styles in L1 versus L2, assessment, and motivation.